Tradable Planning Permits: From an Academic Discourse via a Pilot Project to Planning Practice? - Bovet, Jana; Bizer, Kilian; Henger, Ralph; Ostertag, Katrin; Siedentop, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2013)
For more than 15 years now, researchers and policy makers have been discussing the transfer of trading programs from the regulation of emissions to the regulation of land development. However, the debate remained limited to researchers for a long time, until the German government initiated preparation of a nationwide “pilot project” in 2009. This paper reports on the results of the preliminary project funded by the Federal Environment Agency. An interdisciplinary team developed an outline proposal for the “pilot project”. After a summary of the consequences, benefits and cost of tradable planning permits in general, the paper presents and discusses how the project should be organized in detail. The proposal suggests a controlled field experiment in combination with extensive municipal case studies. The paper concludes with a perspective of the expected outcome of the “pilot project” which has started in 2012.